Direct current heater-assisted triangular solar still for water production - Ahmad, Nur Syuhada (2013)
This study involves the design and development of a panel heater triangular solar still (PHTSS) for producing distilled water from saline and contaminated water. The PHTSS was fabricated with cheap, lightweight and locally acquired and durable materials for easy maintenance. The PHTSS consists of a trough, main frame, polythene cover, support structure, DC heater and solar PV system. A number of field experiments were carried out using seawater, pond water and synthesized salt water of varying salt percentages (1, 2, 3 and 5% salt). The variation of temperatures, relative humidity and the solar radiation were monitored along with the hourly water production. The effect of initial water depth on the production was obtained and an inverse relationship was found between them. Other relationships were also obtained namely, between the daily solar radiation and daily production, between the temperature difference (cover-water) and daily water production, and between the average ambient air temperature and daily production. The water quality analysis of the feed and product water was performed before and after the experiments, respectively. The water quality parameters tested were pH, redox, electrical conductivity, salinity, total dissolved solids (TDS), Escherichia coli (E.coli) and arsenic for feed and product water. The results obtained from the laboratory tests were then compared with various drinking water standards and found that most of the values were within the acceptable ranges provided by the standards. The daily productions of PHTSS are 79.8, 81.3, 77.3 and 43.9% higher than the TSS on July 20, October 1,September 20 and September 24, 2012, respectively. It was found that on average the production of PHTSS is 70.5% higher than the TSS and the highest total daily production of PHTSS is 4.7 kg/m2/day. The relation between the daily water production and the solar radiation shows a positive linear relation, i.e. when solar radiation increases the daily production also increases. A linear proportional relationship is also obtained between the daily production and the temperature difference between water and cover. The relation between the daily production and the salt concentration is inversely proportional, i.e. increasing the salt concentration in feed water will decrease the production. An inverse relationship is also observed between the daily production and the initial water depth. A few models developed earlier (Dunkle, Murugeval et al., Ahsan and Fukuhara) cannot precisely predict the production flux of PHTSS; however the proposed model can reproduce well the production flux. Finally, it is concluded that the PHTSS is capable of producing distilled water from saline and contaminated water and can be applied to remove arsenic, pathogen and TDS as well.